IMPROVING THE QUALITY OF EDUCATION THROUGH TEACHER COMPETENCY DEVELOPMENT: A COMPARATIVE STUDY IN INDONESIA AND MALAYSIA - Taufik, Imam; Hidayatulloh, Hidayatulloh; Rindaningsih, Ida; Zuhro, Sofiatuz; Mahmud, Wan Marfazila Wan; Hairani, Ezza (Antis Publisher, 2025)
Objective: This study aims to conduct a comparative analysis of teacher competency development policies in both Indonesia and Malaysia and identify challenges and supporting factors for their implementation. Method: The method used is a literature review, analyzing policy documents, scientific journals, and official reports. Results: The results indicate that Indonesia emphasizes a decentralized approach through the Merdeka Belajar program and teacher certification, but still faces challenges in access to training and quality equity. Meanwhile, Malaysia implements a centralized approach through the Institut Pendidikan Guru (IPG) and the Program Pembangunan Profesional Berterusan (CPD), with systematic support for technology integration. Both countries face similar challenges, such as infrastructure limitations in remote areas. Novelty: This study recommends strengthening regional cooperation, exchanging best practices, and increasing policy flexibility to address local needs.